A formulation for Gurson's criterion in limit analysis. (July 2021) - Makrodimopoulos, Athanasios
Abstract: Gurson's criterion is widely used in modeling the failure of ductile materials with spherical and cylindrical cavities. A major drawback in terms of numerical treatment in limit analysis is that it contains exponential terms, and thus, the use of second-order cone programming is either not possible or not as straightforward as with other popular yield criteria. This paper presents a formulation of conic optimization with both quadratic and exponential cones, a promising recent development in mathematical programming. Numerical applications in plane strain confirm the efficiency of this approach. Highlights: Gurson's criterion is represented by quadratic and exponential cones. The solution of highly discretized limit analysis problems within short CPU time. Tight lower and upper bounds are obtained.